2015
DOI: 10.24297/jac.v11i6.852
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Electrochemical studies on the corrosion of mild-steel, copper and zinc in 0. 5 M H2SO4 solution in presence of Azithromycin as effective corrosion inhibitor

Abstract: Azithromycin has been tested as inhibitor for steel, copper and zinc corrosion in 0.5 M H2SO4 using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. The results showed that the inhibition efficiency increased with increasing the concentration of Azithromycin. The adsorption characteristics of Azithromycin in presence of steel, copper and zinc metals were studied and the data found to fit the Kinetic-Thermodynamic model. IR spectroscopy of the corrosion product with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Thus, some non-or low-toxic alternatives must be developed to replace traditional hazardous inhibitors. In recent years, some pharmaceutical drugs were recommended for such a purpose such as azithromycin [2], amoxicillin [3], cefixime [4], ciprofloxacin [5], amlodipine [6], oxytetracycline [7], doxycycline [8], norfloxacin [9], enrofloxacin [10], amifloxacin [11], pefloxacin [12], penicillin V [13], ampicillin [14], cloxacillin [15] and flucloxacillin [16]. All these pharmaceutical compounds are rich in heteroatoms like nitrogen, sulphur and oxygen,  bonds and/or aromatic rings, which are major adsorption centres in good corrosion inhibitors.…”
mentioning
confidence: 99%
“…Thus, some non-or low-toxic alternatives must be developed to replace traditional hazardous inhibitors. In recent years, some pharmaceutical drugs were recommended for such a purpose such as azithromycin [2], amoxicillin [3], cefixime [4], ciprofloxacin [5], amlodipine [6], oxytetracycline [7], doxycycline [8], norfloxacin [9], enrofloxacin [10], amifloxacin [11], pefloxacin [12], penicillin V [13], ampicillin [14], cloxacillin [15] and flucloxacillin [16]. All these pharmaceutical compounds are rich in heteroatoms like nitrogen, sulphur and oxygen,  bonds and/or aromatic rings, which are major adsorption centres in good corrosion inhibitors.…”
mentioning
confidence: 99%
“…From the data in Table S2, Supporting Information, it can be found that i corr gradually becomes smaller and the inhibition efficiency gradually rises with increasing Azi concentration, which is consistent with previous research. [ 41 ] Among them, the inhibition efficiency ( η ) can be calculated by the following equation. [ 53 ] η0.33embadbreak=false(icorrfalse)00.33em0.33emicorr(icorr)00.33emgoodbreak×0.33em100%$$\begin{equation}\eta \ = \frac{{{{({i}_{{\mathrm{corr}}})}}_0\ - \ {i}_{{\mathrm{corr}}}}}{{{{({i}_{{\mathrm{corr}}})}}_0}}\ \times \ 100{\mathrm{\% }}\end{equation}$$where (i corr ) 0 and i corr are self‐corrosion current of Zn electrode in ZnSO 4 electrolyte without and with Azi, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…From the data in Table S2, Supporting Information, it can be found that i corr gradually becomes smaller and the inhibition efficiency gradually rises with increasing Azi concentration, which is consistent with previous research. [41] Among them, the inhibition efficiency (𝜂) can be calculated by the following equation. [53] 𝜂 =…”
Section: Her Suppression and Uniform Zn Deposition Benefiting From Zn...mentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7]. Most recently, Tobramycin acts as an anti-corrosive agent on carbon steel in an acidic medium with inhibition efficiencies of 80 %, 90.5 %, 84.3 % [8 ]; the antibiotic Azithromycin acts as an inhibitor for corrosion of mild steel, copper and Zinc in a 0.5 M H2SO4 [9]. Also, the corrosion behavior of Aluminum is studied from antibacterial drugs [10], Nifedipine drug [11], The surface morphology was also investigated to observe any change in the microstructure of the heat-treated specimens produced after corrosion immersion test in an aggressive 3.5% NaCl medium.…”
Section: Introductionmentioning
confidence: 99%